Rethinking contending themes in indigenous and Christian religions in contemporary Africa - O.C. Eze; L.I. Ugbudian; T.A. Adihikon; S.O.S. Nnabuchi; J.U. Eke; C.J. Okolo (Acta Theologica)
Despite myriad of studies on the interface between Christianity and African Indigenous Religion (AIR), there still is an unexplored lacuna in contending themes. In the vast majority of deficit-prone literature, such themes as symbolism, liturgy, sacrifice, saints, sinners, and ontology, among others, are far from balanced. The extant gap has further increased the befuddling perception of African traditional religion by indigenous Christians as belonging to the “Kingdom of Satan” that needs salvation through the instrumentality of Christianity. But irrespective of the waves of evangelism in the continent, many Africans have remained attached to their indigenous religious practices. There has been continuity in practice because the two religions’ themes are similar in content, context, and teachings. This study intends to provide insightful knowledge and awareness about some of these themes and their meeting points. This knowledge will bridge the gap between the two religions and highlight Africa’s contributions to human ideas and civilisation.